The Relationship Between Larynx Cancer and MicroRNAs - Murat Kaya; Ömer Faruk Karataş (Van Tıp Dergisi, 2020)
Larynx cancer (LCa) is the most common malignancy of the head and neck neoplasms accounting for nearly 1% to 2.5% of all human cancers. Almost 95% of these type of cancer originate from squamous cells. Many predisposing factors have been associated with LCa, including smoking and alcohol consumption that are the most common ones. Although many therapeutic advances in the last twenty years have been achieved, the clinical outcome for cases with advanced LCa has not improved. MicroRNAs are endogenously synthesized, single-stranded and non-coding short RNAs of about 18-24 nucleotides in length. MicroRNAs, which play critical roles in the development of many diseases, especially cancers, affect important mechanisms during LCa initiation and progression. Numerous studies have shown that the changes in the expression of various tumor suppressor and oncogenic microRNAs could be involved in laryngeal carcinogenesis process. In this review, findings of recent researches revealing the relationship between LCa and microRNAs are discussed.